P245 Identifying predictors of short-term response to rituximab in extra-glandular primary Sjogren's Syndrome. (23rd April 2022) - Pepple, Sophanit; Arnold, Jack; Vital, Edward M; Rawstron, Andy C; Pease, Colin; Dass, Shouvik; Emery, Paul; Yuzaiful, Md; Yusof, Md
Abstract: Background/Aims: Randomised controlled trials (RCTs) of rituximab (RTX) in primary Sjogren's syndrome (pSS) have failed to alleviate glandular symptoms and fatigue. The question remains as to whether B-cell depleting therapies have a place for the treatment of pSS. Post-hoc analyses from RCTs showed greater improvement in objective measures such as salivary flow rate, salivary gland ultrasound and histology scores in RTX-treated group vs placebo. Moreover, there are limited data on efficacy of the initial and repeat cycles of RTX on extra-glandular pSS. Here, our objectives were to assess the effectiveness of RTX on extra-glandular symptoms and identify predictors of short-term response with a view to personalised B-cell depleting therapy in pSS. Methods: A retrospective longitudinal cohort study was conducted in 40 consecutive RTX-treated pSS patients in a single-centre for over 15 years. All patients fulfilled the 2002 AEG criteria and were CCP negative. Clinical response at 6 months was defined as ≥ 3 point reduction of ESSDAI from baseline. B-cell subsets were measured using highly sensitive flow cytometry. Predictors of short-term response were analysed using penalised logistic regression. Results: 38/40 (95%) patients were female, mean (SD) age 54 (13.7) years, median (IQR) disease duration 5 (2-9) years, 39/40 (98%) had positive ANA and 28/40 (70%) were on concomitant immunosuppressant (IS). Mean (SD) ESSDAI at RTX initiation was 11.5 (6.7) and main domains for RTX were articular (73%), skin (23%), haematological (18%), PNS (15%) and lungs (10%). 169 RTX cycles were administered with a total follow-up of 165PY. In Cycle 1 (C1) RTX, the proportion of patient achieving ESSDAI response from baseline was 29/40 (73%; 95% CI 58-87). There were significant reductions in ESSDAI, daily prednisolone dose and IgG levels at 6 months (all p < 0.05). Of C1 responders, 23/29 received retreatment on clinical relapse; of which 8/23 (35%) lost response [secondary non-depletion non-response (2NDNR) associated with anti-RTX antibodies as we previously observed in SLE=4 (17%)]; side effects=1; ineffective=3. Of C1 non-responders, 9/11 were retreated but only 2/9 responded in C2. Overall, 13/40 (33%) discontinued RTX within two cycles. In multivariable analysis, concomitant immunosuppressant [OR 0.07 (95% CI 0.01-0.52); p = 0.010] and achieving compete B-cell depletion in C1 [0.04 (0.02-0.82); 0.036] reduced non-response to RTX. Conclusion: All patients with pSS should be co-prescribed immunosuppressant with RTX and future therapeutics should aim to achieve complete depletion. About one in six pSS patients lose response in repeat cycles which is associated with 2NDNR phenomenon. The use of humanised or next-generation type 2 anti-CD20 antibodies should overcome these issues and improve the clinical response of extra-glandular pSS. Disclosure: S. Pepple: None. J. Arnold: None. E. M Vital: Consultancies; Dr Vital has received consulting fees from Roche. Grants/research support; Dr Vital has received funding for research from Roche. A. C Rawstron: None. C. Pease: None. S. Dass: None. P. Emery: Consultancies; Prof Emery has received consulting fees from Roche. Grants/research support; Prof Emery has received funding for research from Roche. M. Md Yusof: None.